Computer modeling of water purification in bioplateau taking into account biodegradation processes and greenhouse gas emissions (MCIT: Proceedings of International scientific and practical conference, 2025)
The authors’ research concerns the equations of filtration of contaminated water with dispersed particles of organic residues. A review of works, formulation of research tasks and a mathematical model of filtration with consideration of clogging and suffusion processes and biodegradation are carried out. Dependencies for estimating the volume of greenhouse gases released as a result of biodegradation of organic pollution are proposed.Дослідження авторів стосуються рівнянь фільтрації забрудненої води з дисперсними частинками органічних решток. Проведено огляд робіт, постановку задач дослідження та побудовано математичну модель фільтрації з урахуванням кольмотаційно-суфозійних процесів та процесів біодеградації.
Keywords: filtration; bioplateau; biodegradation; emission; greenhouse gases